LOGIKA HUKUM FRASA “ALASAN SANGAT MENDESAK” DALAM DISPENSASI KAWIN MELALUI HARMONISASI UNDANG-UNDANG NOMOR 16 TAHUN 2019 DAN PERMA NOMOR TAHUN 2019 - Nurul Hasanah; Ramadhana Putra Pratama; Y.A. Triana Ohoiwutun; Dominikus Rato (TAHKIM, 2026)
This study examines the normative meaning of the phrase “urgent reasons” (alasan sangat mendesak) in marriage dispensation cases, emphasizing the need for harmonization between Law Number 16 of 2019 on Marriage and Supreme Court Regulation (PERMA) Number 5 of 2019 on Guidelines for Adjudicating Marriage Dispensation Applications. The main issue addressed in this research concerns the ambiguity (vague norm) of the phrase, which leads to varied interpretations among religious court judges, resulting in inconsistent decisions and a weakened principle of legal certainty. Employing a normative juridical approach with a qualitative analysis method, this study draws upon primary, secondary, and tertiary legal materials obtained through library research. The findings reveal that the absence of clear normative indicators in PERMA No. 5 of 2019 causes judges to rely more on social and moral considerations rather than assessing the child’s psychological readiness, indicating that the principle of the best interest of the child has not been fully realized. Therefore, a normative reconstruction is needed by establishing objective criteria, utilizing psychosocial assessment tools, and strengthening judges’ capacity through child protection–oriented training. This research contributes conceptually to the development of Indonesia’s family law system by proposing a model of legal harmonization that integrates legal certainty, substantive justice, and child protection, thereby promoting a more consistent, fair, and human rights–based practice of marriage dispensation. Keywords: Marriage Dispensation, Urgent Reasons, Legal Harmonization